Pilot Whales Attracted to Killer Whale Sounds: Acoustically-Mediated Interspecific Interactions in Cetaceans: - Cure, C.; Antunes, R.; Samarra, F.; Alves, A.C.; Visser, F.; Kvadsheim, P.H.; Miller, P.J.O. (2012)
In cetaceans’ communities, interactions between individuals of different species are often observed in the wild. Yet, due to methodological and technical challenges very little is known about the mediation of these interactions and their effect on cetaceans’ behavior. Killer whales (Orcinus orca) are a highly vocal species and can be both food competitors and potential predators of many other cetaceans. Thus, the interception of their vocalizations by unintended cetacean receivers may be particularly important in mediating interspecific interactions. To address this hypothesis, we conducted playbacks of killer whale vocalizations recorded during herring-feeding activity to free-ranging long-finned pilot whales (Globicephala melas). Using a multi-sensor tag, we were able to track the whales and to monitor changes of their movements and social behavior in response to the playbacks. We demonstrated that the playback of killer whale sounds to pilot whales induced a clear increase in group size and a strong attraction of the animals towards the sound source. These findings provide the first experimental evidence that the interception of heterospecific vocalizations can mediate interactions between different cetacean species in previously unrecognized ways.